Profound functional suppression of tumor-infiltrating T-cells in ovarian cancer patients can be reversed using PD-1-blocking antibodies or DARPin proteins - Foord, Emelie; Klynning, Charlotte; Schoutrop, Esther; Derani, Judith; Krieg, Jennifer; Mörtberg, Anette; Müller, Mischa R.; Herzog, Christel; Schiegg, Dieter; Villemagne, Denis; Fiedler, Ulrike; Snell, Dan; et al. (Journal of immunology research, 2020)
PD-1/PD-L1 blockade has revolutionized the field of immunooncology. Despite the relative success, the response rate to anti-PD-1 therapy requires further improvements. Our aim was to explore the enhancement of T-cell function by using novel PD-1-blocking proteins and compare with clinically approved monoclonal antibodies (mAbs). We isolated T-cells from the ascites and tumor of 17 patients with advanced epithelial ovarian cancer (EOC) and analyzed the effects using the mAbs nivolumab and pembrolizumab and two novel engineered ankyrin repeat proteins (DARPin® proteins). PD-1 blockade with either mAb or DARPin® molecule significantly increased the release of IFN-γ, granzyme B, IL-2, and TNF-α, demonstrating successful reinvigoration. The monovalent DARPin® protein was less effective compared to its bivalent equivalent, demonstrating that bivalency brings an additional benefit to PD-1 blockade. Overall, we found a higher fold increase of lymphokine secretion in response to the PD-1 blockade by tumor-derived T-cells; however, the absolute amounts were significantly lower compared to the release from ascites-derived T-cells. Our results demonstrate that PD-1 blockade can only partially reinvigorate functionally suppressed T-cells from EOC patients. This warrants further investigation preferably in combination with other therapeutics. The study provides an early pilot proof-of-concept for the potential use of DARPin® proteins as eligible alternative scaffold proteins to block PD-1.
Gesehen am 29.09.2020